2022
DOI: 10.3390/ma15228135
|View full text |Cite
|
Sign up to set email alerts
|

Influence of UV Ageing on Properties of Printed PLA Containing Graphene Nanopowder

Abstract: The present paper analyses the properties of printed polylactic acid (PLA) samples with admixtures of graphene nanopowder (GNP) at wt. 1%, 2% and 4%. The pure polylactide and admixed polylactide printed samples were examined to determine their chemical-physical properties, stiffness, and strength parameters. The tests of tensile, dynamic mechanical analysis (DMA), difference thermogravimetric (TG), and differential scanning calorimetry (DSC) were executed before and after UV (ultraviolet) treatment. The first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Samples were placed in a special chamber constructed by our team with an Hg UV-C 11 V lamp, horizontally at 90° to the UV radiation. Samples were placed on a very thin support made from aluminum; additionally, the chamber walls and bottom were lined with an aluminum mirror in such a way that the UV radiation had access to the samples from all sides and from the bottom [ 16 ]. Air circulation was forced to prevent the formation of ozone, which can accelerate the degradation of PLA, from oxygen by UV irradiation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were placed in a special chamber constructed by our team with an Hg UV-C 11 V lamp, horizontally at 90° to the UV radiation. Samples were placed on a very thin support made from aluminum; additionally, the chamber walls and bottom were lined with an aluminum mirror in such a way that the UV radiation had access to the samples from all sides and from the bottom [ 16 ]. Air circulation was forced to prevent the formation of ozone, which can accelerate the degradation of PLA, from oxygen by UV irradiation.…”
Section: Methodsmentioning
confidence: 99%
“…PLA, like most polymers, is sensitive to UV irradiation, which decreases its lifespan [ 16 ]. PLA degrades due to the intervention of weathering factors (water, UV irradiation) [ 6 , 17 ], and the degradation time depends on the degree of crystallinity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of graphene can affect the biodegradability of PLA. The production methods and chemicals used to prepare graphene and PLA/graphene composites may have adverse environmental effects that need to be considered [55] …”
Section: Toxicity Of Pla/graphene Nanocompositesmentioning
confidence: 99%
“…The production methods and chemicals used to prepare graphene and PLA/graphene composites may have adverse environmental effects that need to be considered. [55] Further research is required to fully understand the toxicity, long-term effects, and environmental risks associated with PLA/graphene nanocomposites. However, current studies indicate the need for safety measures when handling these composites, considering the potential health risks from inhalation or long-term exposure, and exploring more sustainable alternatives.…”
Section: Nanocompositesmentioning
confidence: 99%
“…While some studies have shown that graphene-reinforced PLA poses poor mechanical properties, others have reported that by changing the raster orientation or using larger nanoplatelets, its capabilities may be improved [ 2 ]. Similarly, researchers have investigated the benefits of integrating essential oils or chemically prepared agents for enhancing the dispersion degree for both PLA/GNP [ 12 , 44 ] and PLA/GNP/HA mixtures [ 34 ]. These studies reported that even though the proportion of GNP was reduced to 1–4 wt.% for PLA/GNP and to 0.01–0.1 wt.% for the PLA/GNP/HA samples, the improvements in the mechanical behaviour were signalled only at the lowest amounts of GNP, in opposition to what was expected.…”
Section: Introductionmentioning
confidence: 99%